Super‐Clausius–Clapeyron scaling of rainfall in a model squall line - Singleton, Andrew; Toumi, Ralf (Quarterly journal of the Royal Meteorological Society, 2013)
The sensitivity of squall rainfall to changes in atmospheric temperature is investigated. For instantaneous rainrates and accumulations up to one hour, extreme rainfall scales with Clausius‐Clapeyron (CC) for temperatures below 24°C and at up to twice CC above 24°C. For longer accumulation periods and higher temperatures the scaling breaks down due to increased propagation of the squall line. For all periods, the storm average rainfall is found to scale at approximately 1.5 times CC over the entire range of temperatures. These results have implications for design parameters for infrastructure that is vulnerable to flooding and for climate change projections. Copyright © 2012 Royal Meteorological Society